Seed stocks of grazed and ungrazed rangelands on Palandoken Mountains of Eastern Anatolia - Bakoglu, Adil; Bagci, Eyup; Erkovan, Halil I.; Koc, Ali; Kocak, Alpaslan (Wfl Publ, 2009)
The seed stocks in soil of rangelands community was studied in order to provide a basis for a better understanding of the background of botanical composition. Soil seed stocks changed depending on management strategies efforts and some environmental factors in rangeland sites. Knowledge about soil seed banks and vegetation in these ecosystems was crucial for guiding the restoration efforts. This study examined the size, composition and species richness of the soil seed banks in grazed and ungrazed sites. Forty seven species of botanical composition of the seed stocks were identified, 29 species of them were common to both sites. Seedling number in grazed site was higher than in ungrazed site in the soil stocks. Seeds of desirable grasses and legume species were higher in the grazed site. Similarity index of seedling composition between grazed and ungrazed site was 57.11 %. The results implied that under current grazing condition on the rangelands in the region, range vegetation was not extremely degraded and may be regenerated by soil seed stocks in the case of unexpected degradation event.
Keywords: Soil seed bank; species number and composition